LINGOCULTURAL FEATURES OF CULINARY TERMS IN ENGLISH AND UZBEK LANGUAGES (Conference Zone, 2022)
The study of phraseological units related to food names as units indicating the cultural value of the English and Uzbek languages is the focus of this article. The language displays the uniqueness of the national culture, with phraseological terms reflecting people's morals and perspectives on life being a prime example. In other words, speech can express the environment in which individuals live, the norms by which they live, and whatever acts they take